A Coach's guide to team building understanding functions, structure and leadership - Smith, Helen; Wall, Tony (Coaching Psychology for Professional Practice.)
In today’s ever-changing workplace, it is important for managers and team leaders to be able to navigate challenges arising from unproductive or dysfunctional behaviour among team members. A Coach’s Guide to Team Building applies a unique coaching perspective to tackle the complex issues facing teams and their leaders. Applying psychology principles in coaching and coaching leadership has the potential to help managers adapt to hybrid teams, flexible working and portfolio careers. With insightful case studies and the utilisation of interview data throughout, this book offers practical tools, solutions to real team problems and shares key learnings from coaching, psychology, and professional practice. The interviewees spanned multiple sectors, with insights into industries such as banking, education and engineering, readers can benefit from the flexible, effective approach to successfully creating and leading teams